(3GTcGdjGJ bjGS GdQCj GdYGe (B:s (3eUQ fehPLG (B/s - (3TheGf, eMeOs ([(3Ohf ecGf(B] :s (3OGQ GdcJH GdYdejI ddfTQ h GdJhRjY ,s, 1999)
(3jJfGhd GTcGdjI bjGS GdQCi GdYGe Ydi gPG GdfMh GdeJYeb aGdcJGH jYQV HUhQI fbOjI dcGaI LhGfH gPg GdGTcGdjGJ ef fhGMj GdefgLjI h GdeYQajI h GdCNdGbjI efGbTG hLgGJ GdfXQ GdeNJdaI h GdehGba GdeJTGHcI Mhd GSJWdGYGJ GdQGj GdYGes
Keywords: (3LOGhds; (3GdQCj GdYGes